Use of videogrammetry to estimate length to provide population demographics of dwarf minke whales in the northern Great Barrier Reef - Dunstan, A.; Sobtzick, S.; Birtles, A.; Arnold, P. (J. Cetacean Res. Manage., 2023)
Commercial swim-with-whale programmes, based on the dwarf minke whale (Balaenoptera acutorostrata), have been conducted in Great Barrier Reef waters since 1996 and under permit since 2003. Evaluating the effectiveness of management requires information on the biology of the whales, including possible impacts on their critical life stages, such as mating or calving. In this study, length measurements have been used as the best available proxy for age and thus state of sexual maturity. Underwater videogrammetry was used to estimate the lengths of dwarf minke whales interacting with boats and swimmers during June/July 2003 and 2004. The calibrations used to correct systematic biases in distance and length estimates are presented and other sources of error associated with the methodology and the behaviour of the whales are discussed. Mean lengths (from replicate measurements of individually identified whales) ranged 4.82-6.61m in 2003 (n=23, from five encounters) and 4.48-7.18m in 2004 (n=56, from 29 encounters). The overall mean length (2003: 5.90m; 2004: 5.73m) did not differ significantly between years. In both years, the mean lengths of the majority of whales (2003: 57%; 2004: 59%) were less than 6m, which is regarded as sexually immature based on available life history data. The size ranges within a single encounter were broad; no encounter was dominated by one size class. Segregation by size was not observed. This paper presents the first field measurements of dwarf minke whales on their tropical wintering grounds. While most whales interacting with vessels or swimmers were immature, adult whales, including cow-calf pairs, also were involved. More information, especially on cumulative effects, is needed to assess the impact of these swim-with programmes.